Antiviral Activity of Isoquinolone Derivatives against Influenza Viruses and Their Cytotoxicity - Jang, Yejin (Pharmaceuticals (Basel), 2021)
Influenza viruses are one of the major causative agents for human respiratory infections. Currently, vaccines and antivirals approved for preventing and treating viral infections are available. However, limited protection efficacy and frequent emergence of drug-resistant viruses stand for a need for the development of antivirals with different chemical skeletons from existing drugs. Screening of a chemical library identified an isoquinolone compound (1) as a hit with 50% effective concentrations (EC(50)s) between 0.2 and 0.6 µM against the influenza A and B viruses. However, it exhibited severe cytotoxic effects with a 50% cytotoxic concentration (CC(50)) of 39.0 µM in canine kidney epithelial cells. To address this cytotoxic issue, we synthesized an additional 22 chemical derivatives. Through structure-activity, as well as structure-cytotoxicity relationship studies, we discovered compound 21 that has higher EC(50) values ranging from 9.9 to 18.5 µM, but greatly alleviated cytotoxicity with a CC(50) value over 300 µM. Mode-of-action and cell type-dependent antiviral experiments indicated that it targets viral polymerase activity and functions also in human cells. Here, we present a new class of viral polymerase inhibitors with a core skeleton of isoquinolone, of which antiviral activity could be better improved through following design and synthesis of its derivatives for drug development.